PELELANGAN ATAS BARANG JAMINAN GADAI DALAM HAL TIDAK MENCUKUPI PELUNASAN HUTANG DEBITUR PADA PT. PEGADAIAN (Persero) DI KOTA DENPASAR - Nardian Andryanthi, Luh; -, Adiwati; Westra, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
In this paper was reviewed about an auction for pawning guaranteed goods in term of unfulfilled settlement of debtor’s obligation in PT. Pegadaian (Persero) at Denpasar city. The method which was used by the researcher in this paper writing was descriptive method. This paper was arranged based on empirical legal research. The regulation was used in this paper were Kitab Undang-Undang Hukum Perdata (Burgerlijk Wetboek) and Pedoman Operasional Kantor Cabang Pegadaian. The result of this research was a problem which faced out by Pegadaian in pawning practice mostly in low intensity of buyer interest. However the quite high settled basic price form main office of Pegadaian and the auction’s goods did not sell out could affect the unfulfilled debtor’s obligation settlement. Therefore, it was possible for Pegadaian to do persuasive approach to the debtor’s for paying their remnant obligation. However, if the debtor’s could not pay their obligation, the auction goods would be bought by Pegadaian and be the company asset.
Keywords: pawning guaranteed goods, auctioning in Pegadaian, debtor’s obligation settlement